Molecular Phylogeny and Modelling Distributions of Limnonectes leporinus Populations in Sarawak - Julius, Georgy (-, 2024)
Pagma frog, Limnonectes leporinus, is an endemic species of Borneo, faces significant challenges due to habitat fragmentation caused by deforestation and human activities in Sarawak, Malaysia. As a stream-dependent species, L. leporinus relies heavily on water bodies and forested areas, thus acts as a bio-indicator for healthy forests. This species is a subject of conservation concern, although it is still categorised as least concern (IUCN Red List), due to its declining populations. Conservation efforts require an understanding of the genetic diversity and habitat connectivity of L. leporinus. Therefore, this study aims to evaluate the genetic diversity of L. leporinus populations and develop an informative connectivity model for conservation strategies. By using mitochondrial DNA, Cytb, as molecular marker, 62 samples across 12 localities in Sarawak were analysed. Predictor variables such as land cover, annual temperature, and human population density, were used to develop a habitat suitability model in MaxEnt. Haplotypes data, microhabitat data and MaxEnt result were loaded in Circuitscape to employ habitat connectivity model of L. leporinus. Molecular analysis results revealed moderate genetic diversity across populations, with significant gene flow observed between protected areas. However, isolated populations exhibited reduced gene flow, indicating potential vulnerability to environmental changes. The spatial modelling analysis identified key areas for conservation prioritisation, particularly in lowland regions with sustainable stream networks, which are affected by habitat fragmentation. Habitat suitability model revealed that these lowland areas are ideal for L. leporinus breeding sites, while, the connectivity circuits are predominantly found in unprotected areas, making them crucial for conservation efforts. Most of these suitable yet unprotected areas fall under NCR land category. Therefore, conservation efforts should involve the state government and local communities to promote sustainable land use practices that balance between conservation goals and local communities’ livelihood needs. The findings which underscore the need for targeted conservation strategies, can be used to serve as a management strategies model for similar riparian species threatened by habitat fragmentation in Borneo.